2010
DOI: 10.1111/j.1476-5381.2010.00867.x
|View full text |Cite
|
Sign up to set email alerts
|

Possible involvement of GLP‐1(9–36) in the regional haemodynamic effects of GLP‐1(7–36) in conscious rats

Abstract: The incretin hormone, glucagon-like peptide (GLP)-1(7-36), is rapidly cleaved by dipeptidyl peptidase 4 (DPP-4) into GLP-1(9-36), and although it is agreed that most, if not all, of the metabolic effects are attributable to the intact peptide, the degree to which the cardiovascular effects are due to the cleavage product is unclear. The purpose of this study was to measure the regional haemodynamic effects of GLP-1(7-36), and determine the extent to which the cardiovascular effects of GLP-1(7-36) were influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 33 publications
1
26
0
Order By: Relevance
“…Whether the observed increase in blood pressure is due to an increased cardiac output or to an increase in peripheral resistance cannot be determined from the present results. Blood pressure increases after acute intravenous infusion of GLP-1 or exendin-4 have been observed in both conscious (13) and anesthetized normotensive rats (3,4,44). In healthy humans, GLP-1 transiently increases HR (41) or both HR and MAP (11).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Whether the observed increase in blood pressure is due to an increased cardiac output or to an increase in peripheral resistance cannot be determined from the present results. Blood pressure increases after acute intravenous infusion of GLP-1 or exendin-4 have been observed in both conscious (13) and anesthetized normotensive rats (3,4,44). In healthy humans, GLP-1 transiently increases HR (41) or both HR and MAP (11).…”
Section: Discussionmentioning
confidence: 95%
“…In our study, GLP-1 (9 -36)amide did not affect RBF or RVR in vivo, which could be due to differences between the investigated vascular beds. Gardiner et al (13) found no vascular effects of GLP-1 (9 -36)amide in conscious rats in an investigation of the renal and mesenteric circulation. However, they did report vasoconstriction in response to GLP-1 in the renal and mesenteric circulation, which may relate to the experiments being performed in conscious rather than anesthetized rats.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…GLP-1 and GLP-1 receptor (GLP-1R) agonists induce a sustained elevation of BP in rodents [2,3,27], attributable to central and peripheral mechanisms, but not in largeranimal models [28] or apparently humans [29,30]. However, in a recent study, a modest (~5 mmHg) increase in systolic (but not diastolic) BP, associated with an increase in cardiac output attributable to rises in stroke volume as well as HR, was evident in healthy middle-aged men in response to an i.v.…”
Section: Discussionmentioning
confidence: 99%
“…Thus long-term DPP-4 inhibition may have clinical benefits and/or consequences including cardioprotective actions. Effects on contractility, blood pressure, cardiac output and cardioprotection appear to be independent of diabetes [12][13][14][15][16][17][18][19] . A few studies have been published on cardioprotective effect of GLP-1 analogues and DPP 4 inhibitors.…”
Section: Cardiovascular Protection Effect On Myocardial Functionmentioning
confidence: 99%